Eye See Eye Learn The Benefit of Comprehensive Eye Examinations for Preschoolers - Jones, Deborah A; Chiarelli, Catherine A; Robinson, Barbara E; MacDonald, Karen E (Canadian Journal of Optometry, 2012)
Objective: Undetected vision problems in children can lead to permanent vision loss, a condition known as amblyopia. Early detection and treatment of the causes of amblyopia may prevent this vision loss. The objective of this paper is to look for evidence that comprehensive eye examinations upon entry to junior Kindergarten are an effective way to identify and treat vision problems early. methods: Relevant peer-reviewed publications on amblyopia and the importance of comprehensive eye examinations were reviewed. Specific areas investigated include: the prevalence and causes of amblyopia; impact of vision problems on child development and education; impact of amblyopia and/or strabismus on quality of life; and the cost effectiveness of treating amblyopia. The validity of vision screening compared to a comprehensive eye examination was also reviewed. Synthesis:The review suggests that without a complete eye examination many eye or vision problems remain undetected at school entry. Left uncorrected these problems negatively impact child development, education and quality of life. Reduced vision due to amblyopia also restricts future employment opportunities and increases the risk of bilateral visual impairment in adulthood. Examination procedures with high sensitivity and specificity are required to accurately detect these problems. Studies show that amblyopia treatment initiated at an early age is one of the most cost-effective of all health interventions. Conclusion: There is good evidence in the literature that a full eye examination is critical to detect all cases of amblyopia. This and other visual problems can be detected and managed at an early age, which leads to better visual quality of life and economical outcomes. The Eye See Eye Learn program offers the “gold standard” of eye care.